Formulation and Evaluation of Olanzapine Liquisolid Tablets for Improving Dissolution - Pallavi Bhilaji Jire,; Shrutika Krishnadas Patil,; Nilesh Gulab Ahire,; Mansi A. Dhankani,; Amitkumar R. Dhankani,; Sunil P. Pawar, (Asian Journal of Pharmaceutical Research and Development, 2025)
The oral route remains the most preferred method for drug administration due to its ease, cost-effectiveness, and patient compliance. However, drugs with poor aqueous solubility have challenges to oral bioavailability and therapeutic efficacy. Bioavailability is mostly affected by drug dissolution and its release from the dosage form, and it mainly depends on solubility of drug. For the development of new pharmaceutical products, the major issue any pharmaceutical industry faces are solubility, which ultimately results in low bioavailability. There are various methods to enhanced solubility such as micronization, nanonization, self-emulsification, solid dispersion, co-solvency, solid lipid nanoparticles, co-precipitation technique, particle size reduction and complexation all have been used in recent research to increase the solubility of the drug, but the liquisolid compact has demonstrated superior results for enhancing dissolution. Liquisolid technology is a novel and promising approach used to treat low dose with poorly soluble drugs. OLZ is a BCS Class-II drug prescribed for Schizophrenia, depression, and bipolar disorder. The present study aims to enhance the solubility and dissolution rate of Olanzapine using the Liquisolid Compact Technique. Four formulation batches of OLZ liquisolid tablets were prepared using Tween 80 as non-volatile solvent, Fujicalin as carrier material and Aerosil 200 as coating material and evaluated for general appearance, thickness, hardness, friability, Average weight, disintegration, content uniformity, in-vitro drug release. A drug having a low dose can be formulated by this method.